1997
DOI: 10.1097/00042560-199709010-00007
|View full text |Cite
|
Sign up to set email alerts
|

Co-occurrence of AIDS and Tuberculosis: Results of a Database"Match" and Investigation

Abstract: A registries' data match can provide useful information and result in improved validity for both registries. Although women with AIDS initially appeared to have a higher risk of having active TB, additional parallel analyses suggested that this effect was primarily the result of the 1993 expansion of the definition of AIDS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…In addition, lower utilization of health services, poor treatment compliance and low completion rates among drug users may lead to more severe or prolonged tuberculosis, and more transmission in this group [ 2 , 10 , 11 ]. However, IDU by itself may be an independent risk factor for active tuberculosis [ 6 8 , 12 ]. Studies examining the association of IDU with LTBI have yielded mixed results [ 13 – 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, lower utilization of health services, poor treatment compliance and low completion rates among drug users may lead to more severe or prolonged tuberculosis, and more transmission in this group [ 2 , 10 , 11 ]. However, IDU by itself may be an independent risk factor for active tuberculosis [ 6 8 , 12 ]. Studies examining the association of IDU with LTBI have yielded mixed results [ 13 – 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that HIV+ patients have an increased risk of TB infection (Havlir and Barnes, 1999;Colebunders and Lambert, 2002). The cellular immunosuppression induced by HIV infection prepares the entry of Mycobacterium tuberculosis and is a factor of TB recrudescence (Gollub et al, 1997 infected subjects are 20 to 30 times more likely to develop active TB than HIV-negative subjects (WHO, 2018). Also, the obtained prevalence value of TB-HIV coinfection was slightly high among men (15.18%) compared to women (14.28%), more common in the 21 to 49 age group, representing 82.82% of co-infected cases, and also more prevalent among singles and married people as well, with 88.88% of co-infected cases.…”
Section: Discussionmentioning
confidence: 99%
“…19 Thus, linking the AIDS and TB registry data becomes a very important tool to identify AIDS/TB cases, and has been widely used by the state health departments in the United States since the mid 1980s. 1622…”
Section: Discussionmentioning
confidence: 99%
“…To monitor the impact of HIV infection on the epidemiology of TB in a region, AIDS and TB registry data linkage had been widely used by state health departments in the United States. 1622 However, all studies used a deterministic method without reporting its sensitivity and positive predictive value (PPV). A deterministic method uses a combination of algorithms and rules to look for exact agreement on one or more matching variables between data files with the capability to catch some common errors such as typos, phonetic variations, and transpositions.…”
mentioning
confidence: 99%